Rate of clearance of infection is independently associated with clinical outcome in HIV-associated cryptococcal meningitis: analysis of a combined cohort of 262 patients - Bicanic, Tihana; Muzoora, Conrad; Brouwer, Annemarie E; Meintjes, Graeme; Longley, Nicky; Taseera, Kabanda; Rebe, Kevin; Loyse, Angela; Jarvis, Joseph; Bekker, Linda-Gail; Wood, Robin; Limmathurotsakul, Direk; et al. (Clinical infectious diseases: an official publication of the Infectious Diseases Society of America, 2009)
Background—Progress in therapy of cryptococcal meningitis has been slow because of the lack of a suitable marker of treatment response. Previously, we demonstrated the statistical power of a novel endpoint, the rate of clearance of infection, based on serial quantitative cultures of CSF, to differentiate the fungicidal activity of alternative antifungal drug regimens. We hypothesised that the rate of clearance of infection should also be a clinically meaningful endpoint. Methods—We combined data from cohorts of patients with HIV-associated cryptococcal meningitis from Thailand, South Africa, and Uganda, for whom rate of clearance of infection was determined, and clinical and laboratory data prospectively collected, and explored the association between the rate of clearance of infection and mortality by Cox survival analyses. Results—The combined cohort comprised 262 subjects. Altered mental status at presentation, a high baseline organism load, and a slow rate of clearance of infection were independently associated with increased mortality at 2 and 10 weeks. Rate of clearance of infection was associated with antifungal drug regimen and baseline CSF IFN-γ levels. Conclusions—The results support use of rate of clearance, or early fungicidal activity, as a means to explore antifungal drug dosages and combinations in phase II studies. An increased understanding of how the factors determining outcome interrelate may help clarify opportunities for intervention.
Keywords: Rate of clearance; Early fungicidal activity; Cryptococcal meningitis; Cryptococcus; Outcome